Which Inotropic Drug, Dobutamine or Milrinone, Is Clinically More Effective in the Treatment of Postligation Cardiac Syndrome in Preterm Infants? - Korkmaz, Levent; Ozdemir, Ahmet; Pamukçu, Özge; Güneş, Tamer; Ozturk, Mehmet Adnan (American Journal of Perinatology, 2020)
Objective This study aimed to detect which of the two main medicines suggested in the treatment of postligation cardiac syndrome (PLCS)—dobutamine or mirinone—possesses a more therapeutic effect. While doing this, clinicians are provided with a broader perspective on the treatment and follow-up of cases. The desire was to increase the treatability and monitor ability of the cases in question and hence their survivability.Study Design A retrospective review of a cohort of infants with PLCS was conducted between March 2012 and December 2018. In the treatment of infants with PLCS, dobutamine (dobutamine study group-DSG) or milrinone (milrinone study group-MSG) was used. The respiration, cardiac, echocardiography, and perfusion parameters of the cases were assessed both before and after ligation. Based on the data obtained, both the effects of the medicines on PLCS and the difference between their therapeutic effects were studied. The accuracy of prognostication was assessed with receiver operating characteristic analyses.Results PLCS was detected in 29 (34.1%) of 85 patent ductus arteriosus ligation cases in total. Of all the PLCS cases, 13 (44.8%) were treated with dobutamine and 16 (55.2%) with milrinone. It was observed that the effects of the medicines on the respiratory system and cardiovascular system manifested in the third and 6th hour, respectively. It was detected that both medicines had more effect on the systolic blood pressure (SBP) (area under the curve [AUC]: 0.997/0.996, p = 0.001/0.002) than on the diastolic blood pressure (AUC: 0.911/0.843, p = 0.032/0.046).Conclusion Dobutamine and milrinone, two primary medicines that can be used in the treatment of cases with PLCS, possess similar therapeutic effects on this pathology. In addition, their postoperative therapeutic effects on the SBP are more in the foreground.
Keywords: patent ductus arteriosus; postligation cardiac syndrome; preterm infants; dobutamine; milrinone